Studying the Spatial and Temporal Changes of the Surface Urban Heat Island Using Geographic Information Systems (GIS) and Remote Sensing (Mosul City as a Model) (Iraqi National Journal of Earth Science (INJES), 2026)
Surface heat islands are formed due to the increase in surface temperatures of the earth alongside air temperature within urban areas compared to the surrounding suburban and rural areas. This increase is primarily attributed to the concentration of various human activities and prevalent land uses. This study aims to analyze the spatial and temporal variation of surface temperature across different seasons and the reasons for their concentration in specific locations within the study area. In this study, satellite imagery from Landsat-8 was used. The researcher examined all images from the year 2023 for all seasons to select a set of images that align with the nature of the study to determine the surface temperature of the Earth, providing a true representation of the surface heat island in the city of Mosul using Geographic Information Systems (GIS) and remote sensing. Thermal map results showed that surface heat islands. vary from season to season, with the highest values recorded in the fall, ranging between (42-48.6°C). In contrast, the lowest surface temperatures were recorded in the winter, reaching (13.6-17.1°C). The study also indicated that areas with high population density and desert lands are among the regions that fall within the highest temperature ranges compared to others. Furthermore, it was observed that areas adjacent to the Tigris River and forest areas with dense vegetation cover are less hot, indicating a negative relationship where the surface temperature decreases with an increase in vegetation cover.
Keywords: Surface Urban Heat Island, Climate Change, Gis, Mosul City, Urban Areas